Expanding the niche of marine N2 fixers - Landolfi, Angela; Koeve, Wolfgang; Dietze, Heiner; Kähler, Paul; Oschlies, Andreas (2015)
Nitrogen fixation is essential for maintaining the marine fixed nitrogen (N) inventory which regulates ocean productivity. Still, environmental controls of marine N2 fixation are not well understood. Growing slowly, N2 fixers are expected to be competitive only where N supply is low relative to phosphorus (P) with respect to the cellular N:P ratio of non-fixing phytoplankton (R). This is at odds with observed high N2 fixation rates in the oligotrophic North Atlantic where the surface nutrient supply is elevated in N relative to P. Using resource competition theory and a global coupled ecosystem-circulation model, we show that the ability of N2 fixers to invest additional N into the exo-enzymatic break-down of dissolved organic phosphorus (DOP) gives them a competitive advantage in oligotrophic regions of low P supply. Accounting for this mechanism expands the modeled ecological niche of marine N2 fixers and explains the observed pattern of N2 fixation in the oligotrophic North Atlantic.